In Vitro and In Vivo Evaluation of the Effects of Drug 2c and Derivatives on Ovarian Cancer Cells - Marianna Maddaloni; Rossella Farra; Barbara Dapas; Fulvia Felluga; Fabio Benedetti; Federico Berti; Sara Drioli; Mattia Vidali; Maja Cemazar; Urska Kamensek; Claudio Brancolini; Erminio Murano; et al. (MDPI AG, 2024)
Background: The identification of novel therapeutic strategies for ovarian cancer (OC), the most lethal gynecological neoplasm, is of utmost urgency. Here, we have tested the effectiveness of the compound 2c (4-hydroxy-2,6-bis(4-nitrobenzylidene)cyclohexanone 2). 2c interferes with the cysteine-dependent deubiquitinating enzyme (DUB) UCHL5, thus affecting the ubiquitin-proteasome-dependent degradation of proteins. Methods: 2c phenotypic/molecular effects were studied in two OC 2D/3D culture models and in a mouse xenograft model. Furthermore, we propose an in silico model of 2c interaction with DUB-UCHL5. Finally, we have tested the effect of 2c conjugated to several linkers to generate 2c/derivatives usable for improved drug delivery. Results: 2c effectively impairs the OC cell line and primary tumor cell viability in both 2D and 3D conditions. The effectiveness is confirmed in a xenograft mouse model of OC. We show that 2c impairs proteasome activity and triggers apoptosis, most likely by interacting with DUB-UCHL5. We also propose a mechanism for the interaction with DUB-UCHL5 via an in silico evaluation of the enzyme-inhibitor complex. 2c also reduces cell growth by down-regulating the level of the transcription factor E2F1. Eventually, 2c activity is often retained after the conjugation with linkers. Conclusion: Our data strongly support the potential therapeutic value of 2c/derivatives in OC.